2021
DOI: 10.3390/insects12020121
|View full text |Cite
|
Sign up to set email alerts
|

Parasitoid Distribution and Parasitism of the Fall Armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) in Different Maize Producing Regions of Uganda

Abstract: The fall armyworm (FAW) Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) has successfully invaded Africa, where it has significantly impacted maize and sorghum production. Management of FAW in Africa predominantly relies on synthetic insecticides, which are expensive, and negatively impact the environment and beneficial insects. We, therefore, conducted field surveys in Uganda in 2017 and 2019 to identify egg and larval parasitoids of FAW for possible use in integrated pest management (IPM) programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 79 publications
0
27
1
Order By: Relevance
“…This high parasitism rate is likely to represent a correct estimation of parasitoids developing in young larvae. In most other studies, larval parasitism rates were underestimated because a part of the larvae were collected in their last instar, when these parasitoids had already killed their host (e.g., [11,13,36,37]). In contrast, in this study focusing on the collection of younger larvae, the parasitism rates of the guild attacking younger larvae should be more accurate, while parasitoids attacking older larvae, such as tachinid flies, were missed.…”
Section: Discussionmentioning
confidence: 99%
“…This high parasitism rate is likely to represent a correct estimation of parasitoids developing in young larvae. In most other studies, larval parasitism rates were underestimated because a part of the larvae were collected in their last instar, when these parasitoids had already killed their host (e.g., [11,13,36,37]). In contrast, in this study focusing on the collection of younger larvae, the parasitism rates of the guild attacking younger larvae should be more accurate, while parasitoids attacking older larvae, such as tachinid flies, were missed.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that much more work needs to be carried out to improve knowledge of the benefits of integrated pest management [ 24 ], the use of biopesticides and parasitoids [ 28 ], and management strategies such as early planting and proper fertilization that reduce the susceptibility of an agricultural system [ 29 ]. Invasive pests and diseases that can move into an area from over long distances are becoming increasingly common and economically important [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…and Trichogramma sp. Otim et al (2021), reported 13 species of parasitoids that attack S. frugiperda, including Telenomus sp., T. remus, and Platygastridae.…”
Section: Species Of Spodoptera Frugiperda Egg Parasitoidsmentioning
confidence: 99%